A Journey Through the First to Eighteenth Issue of JKAHS - Amgain , Kapil (Journal of Karnali Academy of Health Sciences, 2024)
The Journal of Karnali Academy of Health Sciences (JKAHS) is an official publication of Karnali Academy of Health Sciences (KAHS), a government organization founded in 2011, by an act of the Parliament of Nepal. KAHS was established with the objective of enhancing the quality of healthcare services, medical education, and research in remote and underserved areas of Nepal. The establishment of JKAHS in 2018 is a reflection of commitment of KAHS to these goals, providing a dedicated platform for the dissemination of scientific knowledge and clinical experiences in the health sciences.